INSTRUMENT OF VOLTAGE RATIO AND CHECK OF PHASE DISPLACEMENT - Suechoey, Boonlert; Maleewat, Panya; Saelee, Vichai (Srinakharinwirot University Journal of Sciences and Technology, 2021)
This paper presents an instrument for measuring voltage ratios and testing of phase displacement of 1-phase and 3-phase distribution transformers. Two tests of the measurement included the voltage ratio between the primary to the secondary windings and the connections of phase displacement (vector group) of the 3-phase distribution transformer, according to the PEA standard (vector group Dyn11). The first testing was conducted by measuring the voltage levels at the primary and secondary sides which were converted into AC/DC voltage signals and adjusted to maintain a desired level for a digital conversion. The obtained digital signal was sent to a microcontroller to process the voltage ratio levels between the primary and secondary sides. The second testing was carried out by converting the electrical phase signals between the primary and secondary sides into the digital signals. The output signals of each phase were sent to a microcontroller to process the phase difference of vector group signals. The results from the tests were shown on an LCD monitor, which were accurate in compliance with the manufacturing company and testing standards.